Medicinal weeds in the rice field of Kathmandu Valley, Nepal - Dani, Ram Sharan; Tiwari, Achyut (Himalayan Biodiversity, 2018)
Weed management in the crop field is one of the major challenges of agriculture. It has been reported that new weeds are encroaching crop fields due to anthropogenic activities such as the use of insecticides, pesticides and chemical fertilizer, and also due to climatic changes including warming temperatures, erratic and unseasonal precipitation, flood and landslides. The agricultural history of Kathmandu valley is quite old, which represents one of the highly productive valleys in of Nepal for agricultural crops including rice, indicating the long history of weeds in the region. There are quite a lot number of medicinally important plants found in rice field as weeds. Traditional practitioners are using these weeds in curing diseases as primary health care, and the utilization of weeds is the best method of weed management. The objective of this present study was to enumerate the weeds in and around paddy field and gather their medicinal properties of weeds among the local people of Kathmandu valley in order to assist with the weed management of paddy field. The periodic field survey was conducted in 9 selected sites, 3 from each district (Kathmandu, Lalitpur, and Bhaktapur) during summer 2012-2014 (two times: crop matured seasons and just after harvesting). We found 104 weed species belonging to 36 families in the rice field of Kathmandu valley that have medicine values.